Chronic endometritis. Towards the improvement of diagnostic methods - A.M. Shamilova; I.Yu. Ilina; E.I. Borovkova; Yu.E. Dobrokhotova (LCC «Medicine-Inform», 2021)
A.M. Shamilova, I.Yu. Il'ina, E.I. Borovkova, Yu.E. Dobrokhotova Pirogov Russian National Research Medical University, Moscow, Russian Federation This paper reviews an important issue that significantly affects female fertility, chronic endometritis. This condition is characterized by clinical presentations of various severity and abnormalities of endometrial morphology. The rate of chronic endometritis varies greatly, mainly due to predominantly asymptomatic course and imperfect diagnostics. Pathogenic mechanisms of endometrial inflammation and different views on its effects on female reproductive potential are addressed. Further search for endometrial receptivity markers is needed as these markers will allow for assessing the severity of endometrial damage to develop the algorithm of preconception care. The authors focus on diagnostic techniques for chronic endometritis and their value. Immunohistochemistry of endometrium is a promising tool to be applied to diagnose endometrial inflammation and monitor treatment efficacy. A complex diagnostic approach to chronic endometritis that includes pelvic ultrasound, 20 Doppler ultrasound, assessment of endometrial microbiota, diagnostic hysteroscopy and endometrial histopathology, and evaluation of endometrial receptivity is useful. Keywords: chronic endometritis, termination of pregnancy, infertility, autoimmune processes, chronic inflammation, endometrial structure, immunohistochemistry. For citation: Shamilova A.M., Il'ina I.Yu., Borovkova E.I., Dobrokhotova Yu.E. Chronic endometritis. Towards the improvement  of diagnostic methods. Russian Journal of Woman and Child Health. 2021;4(3):243-249 (in Russ.). DOI: 10.32364/2618-8430-2021-4-3-243-249.